PERAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM DEMOKRASI PEMBANGUNAN DESA - Ummi Natijah Ummi; Afriva Khaidir (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2019)
This study aims to determine how the role of the Village Consultative Board (Badan Permusyawaratan Desa) in development democracy in Sirambas Village, Panyabungan Barat District, Mandailing Natal Regency. This research was conducted due to BPD has not been maximized in carrying out its role and public awareness of the importance of the domocracy of each is lacking, lack of public activity because most people in Sirambas Village do not yet know what the functions and roles of BPD are. The analytical tool used is qualitative. Method this study uses interviews and documentation with research informants, Chairperson of the BPD, Deputy Chairperson of the BPD, Secretary of the BPD, Members of the BPD, Village Head, Village Secretary, community leaders, and the community. Implementation of BPD function did to discussing and designing village regulations, in Sirambas Village. Not working well BPD does not use an existing office to discuss village regulations, but rather conducts deliberations on village regulations an inappropriate places. This research is able to become input and reference for researchers and BPD can better understand order to achieve a goal. Keywords : Democracy, Village Development, Village Consultative Boar